The Optimal Trading and Pricing of Securities with Asymmetric Capital Gains Taxes and Transaction Costs - Dammon, Robert M.; Spatt, Chester S. (Review of Financial Studies, 1996)
This article explores the optimal trading and pricing of taxable securities with asymmetric capital gains taxes and transaction costs. In the long-term region, investors realize all gains below some critical cutoff level, which we derive analytically. In the short-term region, investors defer all gains and, depending upon the time remaining in the short-term region, may also defer small losses. Contrary to common intuition, deferral of short-term losses can be optimal even without transaction costs. The value of tax timing is considerably higher under the optimal trading strategy than under alternative strategies previously analyzed. The impact of offset rules is also explored.